Caries in Outpatients at the Department of Child Health and Dental Clinic of the Provincial Referral Hospital (RSUPP) in Medan during 1971 - 1973 - Sahat Salim; Helena Siregar; Srinita Tanyati; Santi Uli Simanjuntak (Indonesian Pediatric Society, 1976)
Of 3,000 children with dental caries examined at the Department of Child Health and Dental Clinic of the Provincial Referral Hospital in Medan during 1971 -1973, the highest caries percentage is found in the age group of 3-9 years (74.4%); it is also noted that caries is already prevalent in the group of 1 - 3 years (6.2%). Caries can be prevented by giving fluoride topically or orally and by oral hygiene. To prevent further dental decay, conservation or extraction has to be done.